Single Atomic Iron Site Catalysts via Benign Aqueous Synthesis for Durability Improvement in Proton Exchange Membrane Fuel Cells. Issue 4 (1st April 2021) - Chen, Mengjie; Cullen, David A.; Karakalos, Stavros; Lu, Xiner; Cui, Jiang; Kropf, A. Jeremy; Mistry, Hemma; He, Kai; Myers, Deborah J.; Wu, Gang
Abstract : Atomically-dispersed iron-nitrogen-carbon (Fe–N–C) catalysts have arisen as promising candidates for replacing the costly precious metal catalysts in fuel cells but still face some grand challenges, such as insufficient site density and durability. Herein, we report a self-assembly method in an aqueous solution to develop an atomically-dispersed iron catalyst with high oxygen reduction reaction (ORR) activity and stability in acidic electrolytes. As determined by high-resolution transmission electron microscopy (HR-TEM), X-ray absorption spectroscopy (XAS), and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), this benign aqueous synthesis strategy facilitates the formation of homogeneous atomic nitrogen-coordinated iron sites embedded in a popcorn-like porous graphitic carbon matrix. These catalyst properties contribute to the improved ORR kinetic current density and mass transport. By controlling synthesis chemistry, the correlation between structure and property is systematically investigated. The iron content is the most critical material property and can regulate site density and graphitic carbon structures in the catalyst, impacting catalytic activity and stability. The enhanced performance and durability were examined in both acidic aqueous electrolytes and membrane electrode assemblies.